Model-dependent and model-independent approaches for evaluating hepatic fibrosis in rat liver using shearwave dispersion ultrasound vibrometry. (January 2017) - Lin, Haoming; Zhang, Xinyu; Shen, Yuanyuan; Zheng, Yi; Guo, Yanrong; Zhu, Ying; Diao, Xianfen; Wang, Tianfu; Chen, Siping; Chen, Xin
Highlights: We assessed the hepatic fibrosis in rat liver using ultrasound elastography based acoustic radiation force. Both model-dependent and model-independent approaches were used to evaluate liver fibrosis and their performances were compared. The results suggest that the model-independent approach may provide an alternative method to the model-dependent approach for staging liver fibrosis. Abstract: This study assesses gradations of hepatic fibrosis in rat livers using both model-dependent and model-independent approaches. Liver fibrosis was induced in 37 rats using carbon tetrachloride (CCl4 ); 6 rats served as the controls. Shear wave velocity as a function of frequency, referred to as velocity dispersion, was measured in vitro by an ultrasound elastography method called shearwave dispersion ultrasound vibrometry (SDUV). For the model-dependent approach, the velocity dispersion data were fit to the Voigt model to solve the viscoelastic modulus. For the model-independent approach, the pattern of the velocity dispersion data was analyzed by linear regression to extract the slope and intercept features. The parameters obtained by both approaches were evaluated separately using a receiver operating characteristic (ROC) curve analysis. The results show that, of all the parameters for differentiating between grade F0–F1 and grade F2–F4 fibrosis, the intercept had the greatest value for the area under the ROC curve. This finding suggests that the model-independent approach may provide an alternative method to the model-dependent approach for staging liver fibrosis.